TANTANGAN KOPERASI DALAM PERKEMBANGANNYA DI ERA GLOBAL - Arsad Matdoan (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
Based on the result of the research, it can be concluded that in order to face the global development, there are six strategies needed to overcome the challenge: product mix and market coverage, change of product mix, change of market reach, repositioning to consumer perception of cooperative, and product diversification to reach all society. In addition to facing the MEA, the cooperative is now expected to compete with various other economic instruments in the country so declared ready and able to advance compete in the global economic arena. If the above can be done by cooperatives in Indonesia then the global era will be an opportunity that needs to be achieved, because Globalization describes a process of acceleration of wide interaction in the field of politics, technology, economic, social and cultural. So that the era of globalization will be an opportunity for all cooperatives in Indonesia and asean.